A precarious game : the illusion of dream jobs in the video game industry - Bulut, Ergin (ILR Press, an imprint of Cornell University Press, 2020)
"This book reveals the unequal politics of game development as a dream job, which only privileged subjects can enjoy, while many others have to face significant social and individual costs"--